Life Physical activity after breast cancer diagnosis: Systematic review Atividade física após o diagnóstico do câncer de mama: Revisão sistemática - Boing L.* (2016)
© Edições Desafio Singular.This systematic review aimed to analyze the original studies that investigated the level of physical activity (PA) self-reported, and the benefits and associated factors among women in treatment or after treatment for breast cancer (BC). In this way, the search was performed in electronic databases PubMed, Web of Science, Science Direct, OVID and Health Virtual Library used the descriptors [physical activity] AND [breast cancer] in English, Spanish and Portuguese. 21 studies published in English were included, between 2004 and 2014. We could find that most of the women did not reached the recommendations of PA post-treatment, there were no findings related to the prevalence of PA during treatment of BC. Noted an association between PA practice level with age, BMI, education, ethnicity, BC stage, menopause, associated comorbidities, smoking, body image, depressive symptoms and presence of fatigue. Higher incidence of PA to walk was associated with improved quality of life (QOL), decreased level of fatigue and depressive symptoms.